The Relationship Between Maternal Characteristics and the Level of Knowledge of Self-Medication for Diarrhea in Children in Central Bengkulu Regency - Windi Mutiara Putri Herdianto Gumay; Zamharira Muslim; Nadia Pudiarifanti; Reysa Pradifta (JURNAL ILMIAH FARMASI SIMPLISIA, 2026)
Many housewives self-medicate as a first step in treating diarrhea without consulting a doctor. This study was conducted to determine the level of knowledge and the relationship between housewives' characteristics and the knowledge of self-medication for diarrhea in children in Sri Kuncoro Village, Central Bengkulu Regency. The novelty of this study lies in the analysis of the relationship between the demographic factors of mothers and the level of knowledge of safe self-medication for children in rural areas. This study used a quantitative descriptive design with a survey approach. A sample of 86 respondents was selected using Respondents had to meet the inclusion criteria, namely having a child aged 0–12 years, having previously self-medicated a child’s diarrhea, and being able to read, while the exclusion criteria were mothers who did not complete the questionnaire and could not communicate effectively. Respondent recruitment was conducted by obtaining their consent through an informed consent form. Data were collected through a questionnaire that had been tested for validity and reliability, consisting of 18 questions with a Guttman scale. Data analysis was performed using univariate and bivariate methods, employing percentage calculations to describe respondent characteristics and their level of knowledge regarding self-medication for childhood diarrhea. The results showed that the majority of respondents were aged 26–35 years (43.02%), had a high school education (40.70%), and worked as housewives (94.19%). Mothers' knowledge of self-medication for diarrhea was in the good category (81.40%). The relationship analysis showed that the occupation variable had a significant relationship with the level of knowledge (p = 0.03), while age and education did not show a statistically significant relationship. Most respondents had good knowledge about self-medication for diarrhea in children. The occupation factor was significantly associated with the level of knowledge, while age and education were not significant.